2019
DOI: 10.1002/fsn3.1347
|View full text |Cite
|
Sign up to set email alerts
|

Prediction kinetic, energy and exergy of quince under hot air dryer using ANNs and ANFIS

Abstract: This study aimed to predict the drying kinetics, energy utilization (E u ), energy utilization ratio (EUR), exergy loss, and exergy efficiency of quince slice in a hot air (HA) dryer using artificial neural networks and ANFIS. The experiments were performed at air temperatures of 50, 60, and 70°C and air velocities of 0.6, 1.2, and 1.8 m/s. The thermal parameters were determined using thermodynamic relations. Increasing air temperature and air velocity increased the effective moisture diffusivity (D eff ), E u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 67 publications
(150 reference statements)
11
58
0
Order By: Relevance
“…It was observed that the ratio of energy consumption increased from 0.36 to 0.71, as the temperature rose from 50 to 70 °C. Furthermore, the maximum EUR was 0.71 at 70 °C nd a load density of 300 g, while the minimum value (0.36) was obtained at 50 °C and a load density of 200 g. However, the EUR decreases with a decreasing load density at air temperatures of 50-70 °C, but only in correspondence with load densities of 200 to 300 g. Similarly, Abbaspour-Gilandeh et al (2019) showed that air temperature increases with respect to the EUR when quince was dried in a hot air dryer. Akpinar et al (2005) reported that the EUR decreases with a substantial increase in the temperature and air velocity while performing the energy and exergy analyses in a cyclone type dryer for potato slices.…”
Section: Resultsmentioning
confidence: 81%
“…It was observed that the ratio of energy consumption increased from 0.36 to 0.71, as the temperature rose from 50 to 70 °C. Furthermore, the maximum EUR was 0.71 at 70 °C nd a load density of 300 g, while the minimum value (0.36) was obtained at 50 °C and a load density of 200 g. However, the EUR decreases with a decreasing load density at air temperatures of 50-70 °C, but only in correspondence with load densities of 200 to 300 g. Similarly, Abbaspour-Gilandeh et al (2019) showed that air temperature increases with respect to the EUR when quince was dried in a hot air dryer. Akpinar et al (2005) reported that the EUR decreases with a substantial increase in the temperature and air velocity while performing the energy and exergy analyses in a cyclone type dryer for potato slices.…”
Section: Resultsmentioning
confidence: 81%
“…The reason for this decrease in the percentage of shrinkage under microwave power can be the longer time spent for drying pistachio kernels and the more uniform distribution of heat in the samples. Moreover, increasing microwave power results in higher mass transfer and collapse of the cell structure, and eventually, leads to higher shrinkage in the pistachio kernels (Abbaspour‐Gilandeh, Jahanbakhshi, & Kaveh, 2020). Similar results were obtained for apple (Nowacka et al, 2012), almond (Kaveh, Jahanbakhshi, et al, 2018), and melon seed (Golpour et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded the dried carrot β‐Carotene retaining range was 80.4%, pentin methyl and peroxidase residual activity varied from 83 to 95% and 30 to 35%, respectively. Abbaspour‐Gilandeh, Jahanbakhshi, and Kaveh (2020) developed the hot air dryer for drying quince slices at 50°C‐70°C in drying air temperature. It was observed that the effective moisture diffusivity of drying quince slices was varied from 4.1 × 10 −10 m 2 /s to 1.1 × 10 −9 m 2 /s.…”
Section: Introductionmentioning
confidence: 99%